2023
DOI: 10.3847/1538-4357/acaa3e
|View full text |Cite
|
Sign up to set email alerts
|

Formation of an Intermediate Filament Driven by Small-scale Magnetic Reconnection

Abstract: We present the formation process of a filament in NOAA active region 12765 from 2020 June 5 to 8, using observations from the New Vacuum Solar Telescope, the Solar Dynamics Observatory, and the Global Oscillation Network Group. We found that intermittent small-scale magnetic reconnection occurs at the northern part of the filament, and the small-scale magnetic reconnection shows the characteristics of the oscillatory reconnections. During the magnetic reconnection process, a large amount of material is continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…In particular, OR has become one of the leading contenders for the origin of quasi-periodic pulsations from solar flares (McLaughlin et al 2018;Zimovets et al 2021;Kou et al 2022). OR has also become a potential theoretical explanation for the origin of other periodic solar phenomena, including periodicities within solar jets (Hong et al 2019), quasi-periodic flows (McLaughlin et al 2012), periodicities within Type III radio bursts (Cattell et al 2021), filament formation (Sun et al 2023), flux rope formation and disappearance (Xue et al 2019), stellar flare oscillations (Doyle et al 2018), and a possible explanation for spikes and switchbacks observed by the Parker Solar Probe (He et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, OR has become one of the leading contenders for the origin of quasi-periodic pulsations from solar flares (McLaughlin et al 2018;Zimovets et al 2021;Kou et al 2022). OR has also become a potential theoretical explanation for the origin of other periodic solar phenomena, including periodicities within solar jets (Hong et al 2019), quasi-periodic flows (McLaughlin et al 2012), periodicities within Type III radio bursts (Cattell et al 2021), filament formation (Sun et al 2023), flux rope formation and disappearance (Xue et al 2019), stellar flare oscillations (Doyle et al 2018), and a possible explanation for spikes and switchbacks observed by the Parker Solar Probe (He et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…During its years of operation, the NVST has accumulated over 2 petabytes of observational data. This facilitates research on solar observations, for example, for recording the formation of intermediate filaments (Sun et al 2023b), wave trains accompanying solar flares (Zhou et al 2022), and evolution of anti-Hale regions (Xu et al 2022b). Nevertheless, the continually growing data set poses significant challenges to data management, particularly in the area of data retrieval.…”
Section: Introductionmentioning
confidence: 99%